Institutional Ownership, Blockholder Ownership, and the Board’s Tenure to Disclosure of Corporate Governance - Totok Dewayanto; Rahmawati Rahmawati; Djoko Suhardjanto (Ekuilibrium : Jurnal Ilmiah Bidang Ilmu Ekonomi, 2020)
This research was conducted to determine the effect of institutional ownership, blockholder ownership and the Board’s tenure on disclosure of corporate governance in Indonesia. The population is all publicly listed companies listed on the Indonesia Stock Exchange and samples were taken using purposive sampling techniques to produce a total of 152 companies in the period 2016-2017. Using the multiple linear regression test, the results show that institutional ownership and blockholder ownership have a positive effect on corporate governance disclosure, while there is no effect of the Board’s  tenure on corporate governance.